Data Protection Rights of the Child in the Digital Environment - Noneva-Zlatkova, Yordanka; Rangelova, Suzana; Hadzhieva, Petya (Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges, 2025)
Protecting children's personal data from a digital perspective is essential for preserving their privacy and ensuring their online security. The European Union's legal framework ensures the children's data protection by mandating parental consent for processing the personal information of minors under the age of 16 (Article 8, par. 1, Regulation 2016/679). This guarantees that children's personal data is handled with the highest level of care. These protections aim to limit the collection of unnecessary data and provide clear information on how children's data will be used. In addition, platforms are required to implement measures to protect children from exploitation, exposure to harmful content, and unauthorized sharing of data. The authors trace the latest penalties that are imposed on well-known internet platforms concerning the protection of children's data by various supervisory authorities. In this paper, the authors analyse the practice of the CJEU and the ECHR related to the protection of children's personal data and conclude the main challenges and opportunities for solutions in the current digital reality.